Pemberdayaan Ekonomi Masyarakat Melalui Penerapan Nilai-Nilai Adat Banjar - Hamzani, Yusri (Jurnal Manajemen & Budaya, 2024)
This research is motivated by one of the traditions that is still carried out by the Sasak community, namely the banjar tradition. This tradition not only reflects the richness of cultural identity, but also has great potential to become an instrument for community economic empowerment. In the midst of globalization and modernization, the continuation of banjar traditions and the implementation of traditional values ​​and local wisdom in everyday life is crucial to maintain. In conducting this research, the author used observation, interviews and documentation methods to obtain primary data. Meanwhile, for secondary data, the author took it from several literature related to the theme. After conducting extensive research, the author found that the implementation of traditional values ​​and local wisdom in the banjar tradition has a central role in empowering the economy of the Monggas village community. Values ​​such as mutual cooperation, togetherness and social responsibility are a strong foundation for collaboration in developing local economic businesses. Banjar traditions are also a strong social glue in the community. This is the basis for the formation of a strong social network for the economic empowerment of local communities